Larvicidal proficiency of volatile compounds present in Commiphora wightii gum extract against Aedes aegypti (Linnaeus, 1762) - Patel, Krupal; Akbari, Divya; Pandya, Rohan V.; Trivedi, Jigneshkumar; Mevada, Vishal; Wanale, Shivraj Gangadhar; Patel, Rajesh; Yadav, Virendra Kumar; Tank, Jigna G.; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Plant Science, 2023)
Aedes mosquitoes are the major cause of several vector-borne diseases in tropical and subtropical regions. Synthetic pesticides against these mosquitoes have certain limitations; hence, natural, eco-friendly, and safe larvicides obtained from plant resources are used to overcome these. In the present study, the larvicidal efficiency of Commiphora wightii against the fourth instar stage of the dengue fever mosquito Aedes aegypti (Linnaeus, 1762) was studied. The gum resin of C. wightii was collected using the borehole tapping method, and hexane extracts in different concentrations were prepared. The fourth-instar larvae were exposed to the extracts, and percent mortality, as well as LC20, LC50, and LC90, was calculated. Volatile compounds of the hexane gum extract were analyzed by Headspace GC/MS, and the sequence of the acetylcholine, Gamma-aminobutyric acid (GABA) receptor, and octopamine receptor subunit of A. aegypti was obtained. It was found that the hexane gum extract was toxic and lethal for larvae at different concentrations. Minimum mortality was observed at 164 µg mL−1 (10%/h), while maximum mortality was at 276 µg mL−1 (50%/h). The lethal concentrations LC20, LC50, and LC90 were 197.38 µg mL−1, 294.13 µg mL−1, and 540.15 µg mL−1, respectively. The GC/MS analysis confirmed the presence of diterpenes, monoterpenes, monoterpene alcohol, and sesquiterpenes in the gum samples, which are lethal for larvae due to their inhibitory activity on the acetylcholinesterase enzyme, GABA receptor, and octopamine receptor subunit. The use of commonly occurring plant gum for the control of mosquitoes was explored, and it was found that the gum of C. wightii had larvicidal activities and could be potentially insecticidal.